Consumer perceptions on the origin of infant formula: a survey with urban Chinese mothers. Issue 2 (17th May 2021) - Shan, Liran Christine; Li, Chenguang; Yu, Zhongyi; Regan, Áine; Lu, Ting; Wall, Patrick
Abstract: The consumer survey reported in this research paper aims to understand how Chinese mothers learn about and confirm the origin of powdered infant formulas (henceforward formulas), their knowledge level and preferences between formulas from different origins. With globalization, dairy companies can source ingredients for domestic production and manufacture finished products across the world. Chinese consumers are now facing a variety of formulas with different brand origin, main ingredient origin (' nai yuan '), manufacturing origin, and country-of-purchase. Drawing on a large representative sample of Chinese mothers who have purchased formulas, we found that most of them had intensively engaged in learning about and confirming formulas' origin through different strategies. However, they may not interpret related cues correctly: a majority of Chinese mothers incorrectly considered the 'main ingredient origin' as the 'manufacturing place' and could not necessarily recognize between 'foreign' and 'domestic' brands. Among formulas from different origins, authentic foreign branded, produced and packaged formulas showed a high popularity in Tier 1 & 2 cities and among more knowledgeable consumers. In low-tier cities, these products were equally popular as domestically branded and produced formulas using imported milk powders and other ingredients. Formulas directly acquired from overseas markets through unofficial channels were least favoured by consumers. The study shows that Chinese consumers' previous one-sided endorsement towards foreign formulas appears to have weakened. Decisions made by formula companies on the origin of the main ingredient and the place of manufacture would influence product attractiveness, and the segments of Chinese consumers to target.